Ozonation products of zidovudine and thymidine in oxidative water treatment - Funke, Jan (Water Res X, 2021)
Ozonation is an advanced treatment technology that is increasingly used for the removal of organic micropollutants from wastewater and drinking water. However, reaction of organic compounds with ozone can also result in the formation of toxic transformation products. In the present study, the degradation of the antiviral drug zidovudine during ozonation was investigated. To obtain further insights into the reaction mechanisms and pathways, results of zidovudine were compared with the transformation of the naturally occurring derivative thymidine. Kinetic experiments were accompanied by elucidation of formed transformation products using lab-scale batch experiments and subsequent liquid chromatography – high resolution mass spectrometry (LC-HRMS) analysis. Degradation rate constants for zidovudine with ozone in the presence of t-BuOH as radical scavenger varied between 2.8 ∙ 10(4) M(−1) s(−1) (pH 7) and 3.2 ∙ 10(4) M(−1) s(−1) (pH 3). The structural difference of zidovudine to thymidine is the exchange of the OH-moiety by the azide function at position 3’. In contrast to inorganic azide, no reaction with ozone was observed for the organic bound azide. In total, nine transformation products (TPs) were identified for both zidovudine and thymidine. Their formation can be attributed to the attack of ozone at the C–C-double bond of the pyrimidine-base. As a result of rearrangements, the primary ozonide decomposed in three pathways forming two different TPs, including hydroperoxide TPs. Rearrangement reactions followed by hydrolysis and subsequent release of H(2)O(2) further revealed a cascade of TPs containing amide moieties. In addition, a formyl amide riboside and a urea riboside were identified as TPs indicating that oxidations of amide groups occur during ozonation processes.